Supervised Curricular Internship and the development of management skills: a perception of graduates, undergraduates, and professors - Rigobello, Jorge Luiz; Bernardes, Andrea; Moura, André Almeida De; Zanetti, Ariane Cristina Barboza; Spiri, Wilza Carla; Gabriel, Carmen Silvia (Universidade Federal do Rio de Janeiro, 2018)
AbstractObjective: Analyze the perception of graduates, undergraduates and professors about the teaching-learning process of the Supervised Curricular Internship (SCI) of Nursing Undergraduate Courses and in light of the development of management competencies.Method: Qualitative study based on the Mayan content analysis from a questionnaire of objective and discursive questions that evaluated the perception of 87 undergraduates, 280 graduates, and 48 professors from two universities in the state of São Paulo.Results: Four thematic categories emerged from this process and the development of management skills, highlighting the fundamental role of the supervising nurse in SCI and the need for greater presence of professors. Regarding management skills, the subjects emphasized leadership, resource management and performance of bureaucratic functions as essential skills.Final considerations: SCI is an environment that favors learning the profession and developing managerial skills; however, better coordination is required between educational institutions and SCI practice sites.

ResumenObjetivo: Analizar la percepción de egresados, estudiantes de pregrado y docentes sobre el proceso de enseñanza-aprendizaje de la Práctica Curricular Supervisada (ECS) de los Cursos de Grado en Enfermería según desarrollo de las competencias gerenciales.Método: Estudio cualitativo basado en análisis de contenido de Mayan derivado de cuestionario de preguntas objetivas y discursivas, evaluando la percepción de 87 alumnos, 280 egresados y 48 docentes de dos universidades paulistas.Resultados: Surgieron cuatro categorías temáticas acerca del proceso y del desarrollo de competencias gerenciales, evidenciando: el papel fundamental del enfermero supervisor en el ECS; la necesidad de mayor presencia de los docentes; respecto de las competencias gerenciales, los sujetos destacaron: liderazgo, gestión de recursos y desempeño de funciones burocráticas, como esenciales.Consideraciones finales: El ECS constituye ámbito propicio para aprender la profesión y desarrollar competencias gerenciales, aunque resulta necesaria una mayor articulación entre las instituciones de enseñanza y lugares de práctica del ECS.

ResumoObjetivo: Analisar a percepção dos egressos, concluintes e docentes acerca do processo de ensino-aprendizagem do Estágio Curricular Supervisionado (ECS) dos Cursos de Graduação em Enfermagem e à luz do desenvolvimento das competências gerenciais.Método: Estudo qualitativo baseado na análise de conteúdo de Mayan advindo de um questionário de perguntas objetivas e discursiva que avaliou a percepção de 87 discentes, 280 egressos e 48 docentes de duas universidades paulistas.Resultados: Emergiram quatro categorias temáticas acerca desse processo e do desenvolvimento das competências gerenciais, evidenciando: o papel fundamental do enfermeiro supervisor no ECS; a necessidade de maior presença dos docentes; quanto às competências gerenciais, os sujeitos enfatizaram liderança, gestão de recursos e desempenho das funções burocráticas como essenciais.Considerações finais: O ECS constitui um ambiente propício ao aprendizado da profissão e desenvolvimento de competências gerenciais, entretanto, faz-se necessário maior articulação entre as instituições de ensino e locais da prática do ECS.
Práctica Curricular Supervisada y desarrollo de competencias gerenciales: visión de egresados, estudiantes de pregrado y docentes
Estágio Curricular Supervisionado e o desenvolvimento das competências gerenciais: a visão de egressos, graduandos e docentes
Keywords: Clinical Clerkship; Education; Competency-Based Education; Nursing; Estágio Clínico; Educação; Educação Baseada em Competências; Enfermagem